Familial link of otitis media requiring tympanostomy tubes. (11th November 2016) - Padia, Reema; Alt, Jeremiah A.; Curtin, Karen; Muntz, Harlan R.; Orlandi, Richard R.; Berger, Justin; Meier, Jeremy D.
Abstract : Objectives/Hypothesis: Placement of tympanostomy tubes for recurrent or chronic otitis media is the most commonly performed ambulatory procedure in the United States. Etiologies have been speculated to be environmentally based, and studies have suggested a genetic component to the disease. However, no large‐scale studies have attempted to define a familial component. The objective of this study was to determine the familial risk of otitis media requiring tympanostomy tubes (OMwTT) in a statewide population. Study Design: Retrospective observational cohort study with population‐based matched controls. Methods: Using an extensive genealogical database linked to medical records, the familial risk of OMwTT was calculated for relatives of probands (46, 249 patients diagnosed with OMwTT from 1996–2013) compared to random population controls matched 5:1 on sex and birth year from logistic regression models. Results: The median age at time of tympanostomy tube placement was 1 year (interquartile range, 0–2 years). First‐degree relatives of patients with OMwTT, primarily siblings, had a 5‐fold increased risk of OMwTT ( P < 10 −16 ). Second‐degree relatives were at a 1.5‐fold increased risk ( P < 10 –15 ). More extended relatives (third, fourth and fifth degree) showed a 1.4‐fold increased risk ( P < 10 −15 ). Conclusions: In the largest population‐based study to date, a significant familial risk is confirmed in OMwTT, suggesting otitis media may have a significant genetic component given the increased risk found in close as well as distant relatives. This could be influenced by shared environments given a five‐times risk observed in siblings. Further understanding the genetic basis of OMwTT and its interplay with environmental factors may clarify the etiology and lead to better detection of disease and treatments. Level of Evidence: 3b. Laryngoscope, 127:962–966, 2017